Human Capital and the Population’s Education - Bagdanavičius, Juozas; Stankevičius, Petras; Lukoševičius, Vytautas (Ekonomika, 1997)
The paper deals with the concept of human capital. The authors provide an evaluation of it, reasons for its increasing popularity and its methodological impact on research in education as economics. The analysis of the Lithuanian population’s education according to different training levels, changes in students’ sex, problems of further development of university education and educational reform is based on statistical data. Today the main objective is to create a national educational system based on Lithuanian cultural traditions and integrated into the overall European training system.